2018
DOI: 10.15376/biores.13.2.3300-3314
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Wood Fiber-rubber Composites with Reclaimed Rubber

Abstract: This research investigated the use of reclaimed rubber (RR) from waste tires to partially replace the rubber compound (RC) when making wood fiber-rubber composites (WRCs). Ninety panels of WRC containing RR were manufactured with RR contents of 0% to 40%, mixing times of 6 min to 14 min, and vulcanizing temperatures of 150 °C to 170 °C. There were three steps, which were the fiber-rubber mixing, tabletting, and vulcanization molding processes. Four regression equations for the tensile strength, elongation at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The behavior of similar rubber compounds with and without cork granules was compared at different vulcanization temperatures (compounds B and A, respectively). Independently of cork granules being present in the formulation, the results show that the increasing vulcanization temperature diminished the samples' hardness and compression stiffness (Figure 6), as also observed by many authors regarding natural and synthetic rubbers [25,[53][54][55]. These results are in accordance with the obtained rheometer data, where higher values of torque indicate an increased crosslink density of the material, as presented in Figure 7.…”
Section: Vulcanization Temperaturesupporting
confidence: 89%
See 1 more Smart Citation
“…The behavior of similar rubber compounds with and without cork granules was compared at different vulcanization temperatures (compounds B and A, respectively). Independently of cork granules being present in the formulation, the results show that the increasing vulcanization temperature diminished the samples' hardness and compression stiffness (Figure 6), as also observed by many authors regarding natural and synthetic rubbers [25,[53][54][55]. These results are in accordance with the obtained rheometer data, where higher values of torque indicate an increased crosslink density of the material, as presented in Figure 7.…”
Section: Vulcanization Temperaturesupporting
confidence: 89%
“…In general, the introduction of these natural materials has a similar effect to the introduction of common fillers in rubber compounds. Regarding the manufacturing process, some authors investigated the impact of the mixing process and vulcanization variables, such as pressure or temperature, on some mechanical properties of rubber materials with natural fillers [20,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Several natural fibers have been used as reinforcement phase for different polymer matrices [25][26][27], as shown in Table 1 [28][29][30][31][32][33][34][35][36][37]. Among the natural fibers, the jute is currently one of the cheapest and accounts for the highest production volume [28].…”
Section: Natural Fillersmentioning
confidence: 99%
“…A limited number of investigations had been performed toward the natural fiber-TPE composites based on GRT by studying the potential of natural fiber materials as the reinforcement. Shao et al 15 used waste rubber tire to partially replace the rubber compound in producing the composites from wood fiber and rubber. They reported that mechanical properties, water absorption, and processability were improved when the waste rubber tire with less than 20% was added to the composites.…”
Section: Introductionmentioning
confidence: 99%